Short communication. Lactation performance of Duroc gilts under the single farrowing production system - Daza, A.; Riopérez, J.; Ovejero, I. (Spanish Journal of Agricultural Research, 2005)
Twelve Duroc gilts were used in order to study production and composition of milk during the lactation period and the litter performance under the single farrowing production system. Estrus was induced using PG-600 (400 IU of pregnant mare serum gonadotrophin + 200 IU of human corionic gonadotrophin) and the females were artificially inseminated at 171 +/- 6 d and 95.1 +/- 5.6 kg live weight. Daily milk production was determined according to the weigh-suckle-weigh technique at 1, 7, 14 and 21 d of lactation and colostrum and mature milk samples were collected at farrowing and on 8, 15 and 22 d of lactation. The sows net gain during pregnancy was of 49.1 +/- 7.1 kg and during lactation their feed intake was of 3.4 +/- 0.3 kg dE1 and their weight loss was 5.83 +/- 2.5 kg. The production of milk increased in a linear way through the lactation period and the average daily production was very low (4.29 +/- 0.7 kg). The contents of colostrum dry matter, gross energy and proteinwere higher than the mature milk but lower regarding fat and lactose. Dry matter, gross energy, protein and lactose contents in milk did not significantly vary during lactation. Nevertheless, an increase in fat content was found in the eighth day of lactation. The average daily gain in piglets was 130.4 +/- 31.5 g and the milk conversion ratio was 3.47 +/- 0.39 kg kgE1. The protein level in lactation feed did not have a significant influence on sows and piglets performances.